Bahasa Inggris - Shofiyulloh Khoirul anam (Prodi Ekonomi Syariah Universitas Pangeran Diponegoro Nganjuk, 2025)
This background of pesantren is found in many regions in Indonesia. Some are adults and are able to manage their pesantren, but many are also unable to manage their pesantren. But the most important thing is not only the number of pesantren, but how pesantren are able to continue to exist in this modern world by providing evidence of real answers to the problems faced both internally and externally. Departing from the above problems, the author aims to further study the management and development strategy of salaf Islamic boarding schools. Through this article, it is hoped that it can add experience for writers in particular and for readers in general. The research method used in this study is a literature review approach with a case study method. Research methods that aim to describe a particular situation or field analytically, systematically, factually and comprehensively. This Theotitis framework is based on the design of a financial management information system, namely: increasing efficiency, increasing transparency and supporting accountability. The results of this study show that based on the results of the analysis, there are several Islamic boarding schools that have implemented financial management information systems well, such as: Darul Kholidin Islamic Boarding School in Bogor, Putri Al-Muqoddasah Kudus Islamic Boarding School, Adh-Dhuha Sukoharjo Islamic Boarding School, Miftahul Ulum Panyeppen Pamekasan Islamic Boarding School, Al-Baqiyatussa'diyyah Tembilahan Islamic Boarding School, Al-Falah Pemalang Islamic Boarding School, Islamic Boarding School Sirojuth Tholibin Grobogan. Conclusion From this study, the management information system in Islamic boarding schools not only improves financial performance, but also strengthens public trust in the management of funds in Islamic boarding schools.